2019
DOI: 10.17515/resm2019.111me0201
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of silica aerogel content on the mechanical properties of epoxy resin system

Abstract: Disclaimer All the opinions and statements expressed in the papers are on the responsibility of author(s) and are not to be regarded as those of the journal of Research on Engineering Structures and Materials (RESM) organization or related parties. The publishers make no warranty, explicit or implied, or make any representation with respect to the contents of any article will be complete or accurate or up to date. The accuracy of any instructions, equations, or other information should be independently verifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[3][4][5][6][7] There are many of studies reported on improvement of mechanical properties of epoxy-based composites by filling with silica aerogel. [6][7][8][9][10] In addition to mechanical properties, some of the researchers focused on the thermal insulation properties of silica aerogel incorporated epoxy composites. Kucharek et al [2020] revealed that incorporating aerogel particles into the epoxy resin decreased thermal conductivity from about 190 to 130 mW/mK at 5 wt % of silica aerogel concentration.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] There are many of studies reported on improvement of mechanical properties of epoxy-based composites by filling with silica aerogel. [6][7][8][9][10] In addition to mechanical properties, some of the researchers focused on the thermal insulation properties of silica aerogel incorporated epoxy composites. Kucharek et al [2020] revealed that incorporating aerogel particles into the epoxy resin decreased thermal conductivity from about 190 to 130 mW/mK at 5 wt % of silica aerogel concentration.…”
Section: Introductionmentioning
confidence: 99%